ChemInform Abstract: Electrophile‐Promoted Tandem Cyclization of α, β‐Diynyl Ketodiols: A Facile Synthesis of Tetrahalogenated Spiroketals. Issue 26 (1st July 2014) - Zhu, Hai‐Tao; Wang, Jia; Qiu, Zi‐Hang; Wang, Li‐Jing; Zhong, Mei‐Jin; Liu, Xue‐Yuan; Liang, Yong‐Min
Abstract The corresponding products can be further converted via Pd‐catalyzed coupling reactions [cf.